Implementation of the Arizona Pain and Addiction Curriculum: Findings and Implications From a Statewide Evaluation - Villarroel, Lisa; Mardian, Aram S.; Timme, Evan; Rehman, Shakaib; Christ, Cara M. (Frontiers in Public Health, 2021)
Purpose: The U.S. is struggling with dual crises of chronic pain and opioid overdoses. To improve statewide pain and addiction care, the Arizona Department of Health Services and 18 health education programs collaboratively created the evidence-based, comprehensive Arizona Pain and Addiction Curriculum which includes a Toolbox for Operationalization with adult learning theory applications and an annual program survey to assess curriculum implementation. The purpose of this study is to analyze the first year's survey data to better understand the implementation of a novel curriculum across all programs in the state. Materials and Methods: Program surveys were sent 6 months after curriculum publication to all 18 health education programs in Arizona to assess the 6 Ds of curriculum implementation: Degree of implementation, Difficulty of implementation, Delivery methods, Faculty Development, Didactic dissonance and Discussion Opportunities. Results: Responses from all program types (14/18 programs) indicated that there was widespread implementation of the curriculum, with 71% reporting that all ten Core Components had been included in the past academic year. The majority of programs did not find the Components difficult to implement and had implemented them through lectures. Seventy-seven percent of programs did not have a process to ensure clinical rotation supervisors are teaching content consistent with the curriculum, 77% reported not addressing student's didactic dissonance, and 77% of programs did not report asking students about their interactions with industry representatives. Conclusion: In < 1 year after creation of the Arizona Pain and Addiction Curriculum, all program types reported wide implementation with little difficulty. This may represent a first step toward the transformation of pain and addiction education, and occurred statewide, across program types. Further focus on didactic dissonance, problem solving and faculty development is indicated, along with systematic education on pharmaceutical and industry influence on learners. Other programs may benefit from adopting this curriculum and may not experience significant challenges in doing so.